Effect of Fly Ash and Nano-Silica Fume on Soft Clay: Atterberg Limits, MDD, and OMC - Jumaa, Ruqaya M.; Saeed, Khitam A.; Al-Jaberi, Layth A. (Civil Engineering Journal, 2026)
To improve the geotechnical properties of soft clay soil, this study compares and contrasts two types of micro and nano stabilizing additives: fly ash and nano-silica fume. Treatments with fly ash and nano-silica fume were applied to soft clay samples from Basra, Iraq, at varying fly ash concentrations. The samples were then subjected to the treatments. The ASTM requirements were adhered to in the laboratory tests conducted to investigate changes in plasticity characteristics, maximum dry density, and optimum moisture content (OMC). In the course of this research, Atterberg limits and standard compaction tests were undertaken. In accordance with the findings, fly ash reduces MDD (maximum dry density) by increasing the plastic limit and OMC while simultaneously decreasing the liquid limit and plasticity index. On the other hand, nano-silica fume enhances MDD, decreases OMC and the plastic limit, and increases the plasticity index and the liquid limit. The flocculation and dilution of clay particles are both promoted by fly ash, but the significant reactivity of nano-silica fume increases water adsorption and pore filling. The differences in particle size, specific surface area, and interaction mechanisms explain the observed divergent tendencies. Micro- and nanosized additives added to local soft clay at the same dosage were compared and contrasted in this study. This comparative analysis aims to help select the most effective stabilizing agents that either increase soil plasticity or improve compaction properties. The use of such an approach is a new methodological contribution.